Upaya Meningkatkan Mutu Sekolah Melalui Pendekatan Sistemik dan Permasalahan - Wibawati Bermi (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2020)
The quality and quality of education is one of the human needs in building human capital which is the main driver of human resources to achieve goals and provide students with abilities. The quality and quality of education requires serious attention, both by education providers, government and society. Meanwhile, Dedi Supriadi's research on 12 underdeveloped elementary schools in East Java and NTB concluded that the condition of schools, educational facilities and infrastructure, teacher welfare, student physical condition, enthusiasm for learning and student learning outcomes and parental care were very worrying. The problem is how our schools can achieve quality improvement based on certain standards. What approach is more appropriate to improve school quality. Although an approach has been chosen to improve the quality of schools, we also often see other problems and these are real problems faced by schools, often beyond what is ideally designed on paper. These problems include work culture, differences in insight of the actors, operational techniques, and financial support.